Populist conspiracy myths in far-right terrorist manifestos: A transnational perspective - Armin Langer (ELAD-SILDA)
In recent years, there has been a notable rise in the electoral success of far-right populist movements in various Western countries, coinciding with an alarming increase in far-right terrorist attacks. While far-right populists seek to attain power through democratic means, their rhetoric has inadvertently fostered an environment conducive to the growth of extremist ideologies. This article delves into the manifestos published by far-right extremists from the United States, Germany, Norway, and Australia, illuminating how these manifestos mirror and amplify the narratives espoused by far-right populists. Beyond sharing common conspiracy myths, these terrorists often reference one another and populist politicians in their manifestos, further showing the entanglement between far-right populism and extremism. This paper undertakes a discourse analysis of these terrorist manifestos, probing into how right-wing extremists make use of conspiracy myths promoted by the populist right-wing. As far-right terrorism increasingly threatens peaceful coexistence, it becomes imperative to conduct new research that assesses the role of conspiracy myths in fueling terrorism and devises strategies to avert further radicalization.